(untitled) (PerCursos, 2021)
The cultural and natural world heritage located in the Brazilian territory comprises historical and artistic monuments of centuries-old construction and natural sites endowed with abundant biodiversity. Despite the recognized richness of this legacy, its survival is at risk, especially due to exposure to phenomena resulting from climate variability, already perceived in extreme events that hit the country at the beginning of this century. In this scenario it is essential to understand the exposure of this heritage to the effects of climate change, a condition for thinking about preventive and adaptive measures to contain the perceived vulnerabilities.